Culture, Cognition, and Emotion in China's Religious Ethnic Minorities Voices of Suffering among the Yi - Ting, Rachel Sing-Kiat; Sundararajan, Louise (Palgrave Studies in Indigenous Psychology, 2018)
XXVI, 288 p. 55 illus., 54 illus. in color.